Dalla comprensione del testo all’analisi contrastiva delle traduzioni: l’esempio dell’Epodo VII - Francesco Lubian (Annali Online dell'Università di Ferrara. Sezione Lettere)
This paper, which aims to represent an exercise of contrastive analysis of translations, takes into account five of the most recent Italian renditions of Horace’s Epode VI, published by E. Mandruzzato, G. Scaffidi Abbate, F. Bandini, C. Carena, and U. Dotti. After a preliminary close reading of the Latin text, considered as the indispensable basis for research, translations are object of a careful confrontation, which enlightens their strategies of interpretation of the hypotext and can contribute to evaluate their efficacy, at the same time confirming the hermeneutic – as well as didactic – potential of contrastive analysis practices.